Long- term bisphosphonate treatment coupled with ovariectomy in mice provokes deleterious effects on femoral neck fracture pattern and modifies tibial shape. (September 2020) - Monzem, S.; Ballester, R. Y.; Javaheri, B.; Poulet, B.; Sônego, D. A.; Pitsillides, A. A.; Souza, R. L.
No abstract available